Eksprsi CD68 pada Makrofag sebagai Efek Antiinflamasi Ekstrak Etanol Kulit Buah Tamarillo (Solanum betaceum Cav.) (Studi pada Mukosa BukalTikus yang Diinduksi Karagenan) - Bindaputri, Jelita Febrilia; Sudiono, Janti (Fakultas Kedokteran Universitas Trisakti, 2024)
Background Inflammation is one problem in the oral cavity that patients often complain about. Anti-inflammatory drugs are generally used to treat inflammation but these drugs have side effects therefore currently many anti-inflammatory drugs are developed from natural ingredients, one of which is Tamarillo. The flavonoid of Tamarillo fruit peel can inhibit inflammation. Carrageenan is an irritant that is often used as an indicator of inflammation because it has many advantages. Macrophages are innate immune cells that are important in inflammation. Macrophage cluster of differentiation 68 or CD68 expression can be used to detect inflammation activity. The objective of this study is to detect CD68 expression on macrophages as the anti-inflammatory effect of Tamarillo fruit peel (Solanum betaceum Cav.) ethanol extract. Methods This study used biological specimens of in vivo experimental research by observing immunohistochemical preparations of 5 sample groups, diclofenac sodium as a positive control, NaCl as a negative control, and Tamarillo fruit peel extract groups at doses of 70, 140, and 280 mg/kg.BW. Statistical analysis was performed using the one-way ANOVA test. Results There were significant differences (p< 0.05) in CD68 expression between each treatment group on the 24, 48, and 72 hours with the lowest number of expressions on the 72 hours of 280 mg/kg.BW group. Conclusions Ethanol extract of Tamarillo (Solanum betaceum Cav.) fruit peel has an effect on CD68 expression of macrophage cells in the buccal mucosa of carrageenan-induced rats with the most optimal dose of 280 mg/kg.BW on 72 hours.